CONCEPTUAL VISION OF THE CURRENT MECHANISM OF INTERNATIONAL COOPERATION IN THE FIELD OF CULTURE - HOLOLOBOV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to scientifically substantiate and develop conceptual and applied foundations for innovative mechanisms of state management of Ukraine’s international cultural cooperation in the context of hybrid threats, in particular by formalising the author’s definitions of the concepts of ‘digital cultural diplomacy’, ‘international cultural consortia’ and ‘cultural security’. The research methodology is based on a combination of systemic and comparative analysis, content analysis of international legal acts (UNESCO Convention of 1954, UNESCO Convention of 1970, UN Security Council Resolution No. 2347), the study of the national regulatory framework, and the synthesis of interdisciplinary approaches of modern theories of public administration and cultural policy. An analytical review of international experience (EU, Italy, France), Ukrainian strategic documents and specialised scientific literature was conducted. The authors formulated definitions of key concepts, which allowed them to detail the structural and functional characteristics of the relevant mechanisms. As a result, the following were identified: 1) the main organisational, legal, and information and communication tools of digital diplomacy for promoting Ukraine’s cultural policy in the international arena; 2) mechanisms for forming and supporting the activities of international cultural consortia as a platform for multilateral cooperation; 3) algorithms for integrating cultural security mechanisms into the national security system and regulatory and legal consolidation of relevant procedures. A number of practical recommendations have been proposed for public authorities to optimise the institutional structure, improve the effectiveness of interdepartmental coordination, resource provision and the introduction of systematic threat monitoring. The results of the study form the basis for the implementation of effective mechanisms of public administration in the cultural sphere, strengthening cultural security and ensuring Ukraine’s international subjectivity in the context of modern challenges